Previous use of alcohol, cigarettes, and marijuana and subsequent abuse of prescription opioids in young adults. - Fiellin, Lynn E; Tetrault, Jeanette M; Becker, William C; Fiellin, David A; Hoff, Rani A (The Journal of adolescent health : official publication of the Society for Adolescent Medicine, 2013)
There has been an increase in the abuse of prescription opioids, especially in younger individuals. The current study explores the association between alcohol, cigarette, and/or marijuana use during adolescence and subsequent abuse of prescription opioids during young adulthood.